Influencing factors of the participation of patients with severe mental disorders in community health service management - Li, Shiming; Ji, Yingying; Yang, Queping; Jiang, Ying; Yin, Qitao; Zhu, Haohao (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to explore the participation of patients with severe mental disorders in community health service management and its influencing factors in Wuxi.MethodsThe data of patients with severe mental disorders were extracted from the Jiangsu Provincial Management System between 2019 and 2021. The participation of patients in community health service management was analyzed. A univariate stratified analysis will be used to assess the impact of various factors on inclusion in community management. Logistic regression modeling will be employed to identify influencing factors. Ultimately, negative factors affecting participation in community health management will be identified, followed by targeted qualitative analysis through interviews.ResultsA total of 27,977 individuals were included in the analysis, with 25,744 participants enrolled in community health service management, resulting in a management rate of 92.02%. Multivariate logistic regression analysis revealed the following negative factors influencing participation in community health service management: Age group 31–40 years (OR = 0.532, 95% CI: 0.434–0.653), Age group 41–50 years (OR = 0.557, 95% CI: 0.468–0.663), Age group 51–60 years (OR = 0.746, 95% CI: 0.635–0.877), Age group >60 years (OR = 0.840, 95% CI: 0.719–0.969), Duration of illness 6–10 years (OR = 0.376, 95% CI: 0.307–0.461), Duration of illness 11–15 years (OR = 0.312, 95% CI: 0.249–0.390), Duration of illness 16–20 years (OR = 0.702, 95% CI: 0.529–0.932), Duration of illness >20 years (OR = 0.701, 95% CI: 0.514–0.957), Education level of college or above (OR = 0.719, 95% CI: 0.560–0.923), Current student status (OR = 0.565, 95% CI: 0.419–0.760), Absence of social welfare benefits (OR = 0.643, 95% CI: 0.572–0.723), History of violent or harmful behavior (OR = 0.553, 95% CI: 0.442–0.692), Non-participation in community rehabilitation activities (OR = 0.170, 95% CI: 0.101–0.284). Conversely, the following factors were identified as positive influences on participation: Being a farmer (OR = 1.423, 95% CI: 1.215–1.665), Widowhood (OR = 2.355, 95% CI: 1.583–3.503), Divorce (OR = 2.992, 95% CI: 2.093–4.278). Qualitative analysis indicated that stigma associated with the illness, concerns over information disclosure, lack of social support, impacts on family members (e.g., children's education or marriage prospects), perceived ineffectiveness of community services, lack of awareness about available community health services, and the belief that services were unnecessary contributed to non-participation in community health service management.ConclusionThe participation rate of patients with severe mental disorders in health service management is relatively low in the Wuxi. Special attention should be given to patients with severe mental disorders who exhibit negative factors, such as being middle-aged or young, having a long duration of illness, a history of violent or harmful behavior, higher education levels (college and above), student status, or lack of social welfare benefits. Efforts should focus on providing social support activities, reducing stigma associated with the illness, and further improving the management rate.